2009
DOI: 10.1677/joe-08-0488
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence of immune function modulation by thyroid hormones in healthy men and women aged 55–70 years

Abstract: A reciprocal relationship between the endocrine and immune system has been demonstrated under pathophysiological conditions. However, few studies have assessed the relationship between thyroid hormones and immune function in apparently healthy individuals. Therefore, to clarify our understanding of normal physiological endocrine-immune interactions this study aimed to examine the interrelationships between thyroid hormones and immunity in healthy individuals. Total triiodothyronine (T 3 ), total thyroxine (T 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 38 publications
2
64
1
2
Order By: Relevance
“…In 1973, it was reported that removal of the thyroid gland leads to significant reduction in peripheral lymphocytes, impaired humoral immunity, and reduced sensitivity of lymphocytes to mitogen (Fabris, 1973). Available data from several lines of in vivo and in vitro studies show that functions of almost all immune system cells, including monocytes, thymocytes, lymphocytes, natural killer (NK) cells, and splenocytes, are affected by THs (Csaba et al, 1977;Hodkinson et al, 2009;Mascanfroni et al, 2008;Savino et al, 1990). Tang & Kaptein (1989) were perhaps the first to show that alterations in serum levels of THs modulate host defense against viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…In 1973, it was reported that removal of the thyroid gland leads to significant reduction in peripheral lymphocytes, impaired humoral immunity, and reduced sensitivity of lymphocytes to mitogen (Fabris, 1973). Available data from several lines of in vivo and in vitro studies show that functions of almost all immune system cells, including monocytes, thymocytes, lymphocytes, natural killer (NK) cells, and splenocytes, are affected by THs (Csaba et al, 1977;Hodkinson et al, 2009;Mascanfroni et al, 2008;Savino et al, 1990). Tang & Kaptein (1989) were perhaps the first to show that alterations in serum levels of THs modulate host defense against viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, physiological levels of T 3 were demonstrated to induce the maturation of murine DCs (Mascanfroni et al 2008). Similarly, T 4 was found to be associated with higher concentrations of complement proteins and also higher neutrophil counts (Hodkinson et al 2009). T 4 concentration was also inversely correlated with the ratio of naïve to memory cytotoxic T cells (Hodkinson et al 2009).…”
Section: T Cellsmentioning
confidence: 92%
“…Similarly, T 4 was found to be associated with higher concentrations of complement proteins and also higher neutrophil counts (Hodkinson et al 2009). T 4 concentration was also inversely correlated with the ratio of naïve to memory cytotoxic T cells (Hodkinson et al 2009). Taken together, these results suggest that higher concentrations of thyroid hormones could enhance innate and adaptive immunity, via maintenance of specific subsets and increased responsiveness to immune stimuli (Hodkinson et al 2009).…”
Section: T Cellsmentioning
confidence: 96%
See 1 more Smart Citation
“…Although many types of antithyroid antibodies have been described, the most common is the group of antibodies directed against various parts of the thyroid peroxidase molecule [24][25][26]. Most pregnant women with abnormally elevated serum levels of thyroid peroxidase antibodies are clinically and biochemically euthyroid, but they may be at increased risk of spontaneous abortion, and preterm delivery and other pregnancy complications [11,27].…”
Section: Observationmentioning
confidence: 99%